La calidad de la educación superior en Colombia - Lugo González, Armando (Revista Científica, 2012)
This paper shows the results of the research, “Quality of Higher Education in Colombia in the New World Order”, which intended to make an approach to the problem woven around the fact that higher education has structural problems related to quality, due to its submission to the logic of the market, and specifically this paper tries to solve the question: Why the logic of the market generates structural problems related to quality of higher education in Colombia? In order to achieve this goal, we used the critical discourse analysis methodology, which allowed us to propose an approach to the quality in higher education concept, and also to propose some contradictions that lie when governments try to implement this concept. Finally, we made some proposals and conclusions about this topic.